2015
DOI: 10.1016/j.jip.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Zoothamnium duplicatum infestation of cultured horseshoe crabs (Limulus polyphemus)

Abstract: Please cite this article as: Shinn, A.P., Mühlhölzl, A.P., Coates, C.J., Freeman, M.A., Metochis, C., Zoothamnium duplicatum infestation of cultured horseshoe crabs (Limulus polyphemus), Journal of Invertebrate Pathology (2014), doi: http://dx.doi.org/10. 1016/j.jip.2014.12.002 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Although the development of horseshoe crab aquaculture is still in its infancy, various laboratory studies have reported culture conditions for juvenile horseshoe crab species in experimental investigations (Carmichael & Brush 2012;Shinn, M€ uhlh€ olzl, Coates, Metochis & Freeman 2015). Some of these studies have demonstrated that protein-rich diets of brine shrimp, clams, mussels and polychaetes can enhance the growth performance of juveniles (Carmichael, Gaines, Sheller, Tong, Clapp & Valiela 2009;Schreibman & Zarnoch 2009;Hu, Wang, Cheung & Shin 2012); however, Kwan, Chan, Cheung and Shin (2014) revealed that the haemolymph quality in juvenile Chinese horseshoe crabs under laboratory culture was significantly reduced over a 12-week experimental period even under high-protein diet treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Although the development of horseshoe crab aquaculture is still in its infancy, various laboratory studies have reported culture conditions for juvenile horseshoe crab species in experimental investigations (Carmichael & Brush 2012;Shinn, M€ uhlh€ olzl, Coates, Metochis & Freeman 2015). Some of these studies have demonstrated that protein-rich diets of brine shrimp, clams, mussels and polychaetes can enhance the growth performance of juveniles (Carmichael, Gaines, Sheller, Tong, Clapp & Valiela 2009;Schreibman & Zarnoch 2009;Hu, Wang, Cheung & Shin 2012); however, Kwan, Chan, Cheung and Shin (2014) revealed that the haemolymph quality in juvenile Chinese horseshoe crabs under laboratory culture was significantly reduced over a 12-week experimental period even under high-protein diet treatments.…”
Section: Introductionmentioning
confidence: 99%
“…The observations on the morphology of ectoparasites of mud crabs (S. serrata) and white shrimps (L. vannamei) showed slight differences when compared to those that have been recorded by Ma and Overstreet (2006), Jie et al (2006), Chan et al (2009), Ihwan et al (2014), Xinlu et al (2014) and Shinn et al (2015).…”
Section: Resultsmentioning
confidence: 67%
“…They are known bacterial grazers, hence generally influence bacterial epibiosis. However, the ciliate genus Zoothamnium, which was detected in high abundances on FV is also known as a marine pathogen (Shinn et al, 2015) and may contribute in part to the highly fouled surface observed. Significantly abundant ascomycete genus on FV was the yeast Candida, which might contribute to microfouling and consume algal exudates.…”
Section: Discussionmentioning
confidence: 99%